Hotspots of N2O accumulation in the soil profile of alternate wetting and drying paddy fields - Liu, Guangyan; Chen, Xuda; Chen, Taotao; Chi, Daocai; Zou, Hongtao (Frontiers in Plant Science, 2026)
IntroductionAlternate wetting and drying irrigation (IAWD) is a promising practice for water conservation and climate mitigation, yet it inadvertently stimulates substantial nitrous oxide (N2O) emissions. While previous research has largely focused on surface N2O fluxes, the processes governing N2O accumulation and emission across the soil profile–surface continuum remain poorly understood.MethodsHere, we present a comprehensive dataset from a lysimeter study on paddy fields under IAWD and continuously flooded irrigation (ICF), integrating measurements of soil N2O concentrations (0–50 cm depth, at 10-cm intervals) and concurrent surface fluxes.ResultsThe results showed that N2O predominantly accumulated in 0–20 cm soilprofiles during the tiller fertilizer period (TF) and panicle fertilizer period (PF) regardless of the irrigation regimes. Compared to ICF, IAWD significantly increased the N2O concentrations in 0–30 cm soil profiles by 19.6–49.3% and 60.0–79.0% during the TF and PF, respectively. Partial least-squares path model further identified the 10–20 cm layer as the dominant hotspot, exerting the strongest direct control on surface N2O emissions.DiscussionAltogether, 0–20 cm soil profiles are the hotspots for N2O accumulation in IAWD paddy fields, and the N2O accumulated in 10-20 cm soil profile dominates the N2O emissions. These findings contribute to the adoption of straightforward and targeted N2O mitigation strategies in IAWD paddy fields.